Determination of Physical Workload and the Ideal Number of Workers in Arsy Bakery using Full Time Equivalent (FTE) Method - Setiowati, Noni Oktiana; Zamzani, Muhamad Imron; Nurdiono, Debi (Fakultas Teknik UMRI, 2023)
Arsy Bakery is one of the MSMEs located in Karang Joang, Balikpapan. This bakery produces five types of bread: white bread, sweat bread, mocha bread, cheese chocolate bread, and three-flavored bread. Arsy bakery could produce approximately 4000 loaves of bread weekly. This study aims to calculate the quantity of physical workload of Arsy bakery workers based on Full Time Equivalent (FTE) method and determine the ideal number of workers required. FTE is a workload analysis method that measures the length of time to complete the tasks in production process. The workload quantity for every worker is obtained based on the time measurements and calculation results. Based on the results of this study, the amount of workload that carried out by Worker 1 is 1.67, meanwhile the amount of workload carried out by Worker 2 is 1.60. These values show that both workers can be categorized as overload. The total FTE value for two workers is 3.27 which means that there should be 3 employees to finish Worker 1 and Worker 2 tasks. In conclusion, Arsy Bakery needs to recruit 1 new employee to reduce high workload of the current employees.